PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) PADA POKOK BAHASAN KOLOID MENGGUNAKAN PANTUN DAN TULISAN ARAB MELAYU - Fauzia Rahmi; Usman Rery; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aimed to develop the student’s sheet activity on colloids subject using poetry and writing of arabic malay of valid based on the feasibility aspect of content, language, serve and graphic.. The type of this research was reserach and development (R & D) with the 4-D development model which include Define, Design, Develop, and Disseminate. This research was to develop phase. This research was conducted in FKIP Riau University. The object of this research was the student’s activity sheet using poetry and writing of arabic malay. The data analysis technique used for this research was descriptive statistic descriptive. The descriptive analysis done by calculated the percentage of validation value. The average score of valuation to four expediency aspect of student’s activity sheet by validator’s team, such as the content properness, the language properness, course and the graphical has expediency value continued is 89,81%, 90,28%, 97,92%, and 95,83%. Thus, the average score totality of student’s sheet activity based on colloids subject using poetry and writing of arabic malay is 93,46% which is in valid criteria, means that the LKPD Developed is proper to be use.